Szerb térnyerés a Vajdaságban - Léphaft, Áron (Közép-Európai Közlemények, 2011)
The main goal of the article is to demonstrate the transformation of ethnic space in Vojvodina between 1910 and 2002. The analysis of transformation primarily covers the expansion of Serbian ethnic territory and the shrinking and loosening of spaces inhabited solely or predominantly by minority groups (German, Hungarian, Romanian, Slovak etc). The decrease of minority populations is observable during the whole period in question, mainly because of emigration, assimilation and deportation. The expansion of Serbian ethnic space could be divided into three major cycles; the first and second colonization after the First and the Second World War; and lastly the arrival of refugees after the breakup of Yugoslavia. The above-mentioned events had a strong, often preplanned impact on the spatial structure, which can be traced to the selection of places designated for colonization or displacement. The outlined changes resulted in a much homogenous ethnic space in the province: the Serbian presence rose from 33,8% to 65,1%. More importantly, almost all Serbian-dominated settlements were connected on the map, while the minority-dominated spaces were penetrated, partitioned, or even dissolved.